Surface Anatomy-Based Clavipectoral Fascia Plane Block for Clavicle Surgery - Purnomo, Heri Dwi; Witjaksana, Risnu (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Clavicular fractures are often observed cases. In the majority of clavicle fractures, both in adults and children, the fracture is located in the midshaft. Generally, General Anesthesia techniques are usd in such instances, as regional anesthesia through peripheral nerve block often presents its own challenges. The clavipectoral fascial plane block was first introduced in 2017. Apart from its ease of implementation, the Surface Anatomy-Based Clavipectoral Plane Block can avoid the risks associated with other regional anesthesia techniques such as Plexus Brachialis Block or Interscalene Block. Objective: This report aims to provide an overview of the procedures for carrying out surface anatomy-based clavipectoral fascia plane block for clavicle surgery. Case Report: A 33-year-old man with the primary complaint of pain in the right shoulder following a fall while playing football. The patient was diagnosed with closed re-fracture of the clavicle (D) Allman Group I. Clavicle surgery was conducted with the Surface Anatomy-Based Clavipectoral Fascia Plane Block technique. In this patient, local anesthetic agents were administered as Levobupivacaine 0.375% in a volume of 20 cc. The operation lasts approximately 1.5 hours. The Patient’s hemodynamic condition was stable during the surgery. The patient had no complaints and post-operative pain was effectively managed. Conclusion: The surface Anatomy-based Clavipectoral fascia plane block can be considered for clavicular surgery, especially in Allman Group type 1. Besides being easy to implement, this technique also poses fewer risks compared to other regional anesthesia techniques.